Clinical Significance of the Relationship between Progression-Free Survival or Postprogression Survival and Overall Survival in Patients with Extensive Disease-Small-Cell Lung Cancer Treated with Carboplatin plus Etoposide - Hisao Imai; Keita Mori; Nodoka Watase; Sakae Fujimoto; Kyoichi Kaira; Masanobu Yamada; Koichi Minato (Canadian Respiratory Journal)
Background. The effects of first-line chemotherapy on overall survival (OS) might be confounded by subsequent therapies in patients with small-cell lung cancer (SCLC). Therefore, by using individual-level data, we aimed to determine the relationships between progression-free survival (PFS) or postprogression survival (PPS) and OS after first-line chemotherapies in patients with extensive disease-SCLC (ED-SCLC) treated with carboplatin plus etoposide. Methods. Between July 1998 and December 2014, we analyzed 63 cases of patients with ED-SCLC who were treated with carboplatin and etoposide as first-line chemotherapy. The relationships of PFS and PPS with OS were analyzed at the individual level. Results. Spearman rank correlation analysis and linear regression analysis showed that PPS was strongly correlated with OS (r=0.90, p<0.05, and R2=0.71) and PFS was moderately correlated with OS (r=0.72, p<0.05, and R2=0.62). Type of relapse (refractory/sensitive) and the number of regimens administered after disease progression after the first-line chemotherapy were both significantly associated with PPS (p<0.05). Conclusions. PPS has a stronger relationship with OS than does PFS in ED-SCLC patients who have received first-line chemotherapy. These results suggest that treatments administered after first-line chemotherapy affect the OS of ED-SCLC patients treated with carboplatin plus etoposide.